What Do Patients Want To See On Social Media? Evidence From A Two-Year Experiment - Leire Barrutia; Jes´ús Vega-Gutiérrez; Alba Santamarina-Albertos (Mattioli1885, 2023)
Introduction: Dermatological information on social media is dominated by misleading and potentially harmful content from nonexperts. Literature suggests that, to address this issue, dermatologists should develop an online presence. However, successful presence of dermatologists on social media has been criticized for focusing on cosmetic dermatology and not representing the broad spectrum of the specialty. Objectives: The aim of this study was to systematically analyze which dermatological topics interest the public most, and to find out whether it is feasible for a dermatologist to become influential on social media while presenting all dermatological topics equally. Methods: The study was performed on an educational dermatology YouTube channel. The 101 videos published in a two-year period were divided into cosmetic (51 videos) and medical dermatology (50 videos). Student's t-test was conducted to determine whether there were significant differences in views. Medical dermatology videos were then classified into three categories: Acne, facial dermatoses (excluding acne) and other dermatological diseases. A Kruskal-Wallis test was used to compare these three categories and cosmetic dermatology. Results: When comparing cosmetic and medical dermatology, no significant differences were found. When comparing the four categories, cosmetic dermatology and acne were found to generate significantly more views that other dermatological diseases. Conclusions: The public seems to be particularly interested in cosmetic dermatology and acne. This might make it challenging to become successful on social media while presenting a balanced portray of dermatology. However, focusing on popular topics can provide a real chance to be influential and protect vulnerable people from misinformation.